(3QSGdI aj JQLeI CHh GdMSjf Ydi Hf YHO GdQMefs - (3eMeO Hf GdWjH Hf YHO GdSdGe GdMSfj GdbGOQj , CHh YHO Gddg,J (B1187 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hef NWg CjVkG eG fUg GdMeO ddg CHh GdMSjf Ydi Hf YHO GdQMef s
(3BNQgG (B:s
(3hEPG HGdhHGA CJi hWYfg aeGJ efg ceG CNHQfG SjOfG CMeO ef NW GdYdGeI GdePchQ cGf Gddg dfG hdg hdLejY GdeSdejf Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B109s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(370 d) s
Keywords: (3GdeLGejYs